CHARACTERISTICS OF INTERTROCHANTERIC FEMUR FRACTURE AT BALI MANDARA GENERAL HOSPITAL - Prabawa, I Made Ngurah Angga; Sanjaya, Putu Agung Wirahadi; Kenwa, Komang Wiswa Mitra (Jurnal Ilmu Kedokteran dan Kesehatan, 2024)
Abstract: Characteristics of Intertrochanteric Femur Fracture at Bali Mandara General Hospital. An intertrochanteric femur fracture is an extracapsular fracture that occurs along the line that is located between the greater and lesser trochanters. This study aims to determine the characteristics of intertrochanteric femur fracture cases. This retrospective descriptive study evaluated the characteristics of intertrochanteric femur fracture patients at Bali. Mandara General Hospital Denpasar from January to August 2022. There were 36 intertrochanteric femur fracture patients (8.78%). Intertrochanteric femur fracture patients are mostly found in female patients (25 patients [69.4%]) and the elderly. Based on the mechanism of trauma, 33 patients had a fracture due to low-energy trauma. According to Boyd and Griffin’s classification, type 2 intertrochanteric femur fracture was more common (14 patients [38.9%]). All patients had PFNA (100%) and most of them had a grade B Singh index (16 patients [44.4%]). The incidence of intertrochanteric femur fracture was 8.78%. The intertrochanteric femur fracture was more common in the female patient, aged more than 60 years old, occurs due to low energy trauma, has a type 2 Boyd and Griffin classification, has a grade B Singh index, and was treated using PFNA.